2020
DOI: 10.3390/w12061759
|View full text |Cite
|
Sign up to set email alerts
|

Modelling PAHs Transfer from Polluted Soil to Herbaceous Species in Phytoremediation Attempts

Abstract: To address the soil–plant transfer modelling of 13 US-EPA Polycyclic Aromatic Hydrocarbons (PAHs), a mechanistic model—MM_19—has been developed based on the fugacity concept. For that, the Mackay_97 model has been improved in terms of reconsidering the losses related to the transport and transformation mechanisms taking place in the compartments—roots and aboveground shoots—of the three short-life species (Eleusine indica, Cynodon dactylon and Alternanthera sessilis). Model input parameters consist of both exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…It is also interesting to note that numerous factors can dramatically alter the percentage contributions of ΣPAHs(3,4) and ΣPAHs(5,6). The influence of PAH molecular weights on the soil-plant transfer of PAHs was investigated using three short-life herbaceous species, namely Eleusine indica , Cynodon dactylon , and Alternanthera sessilis ( Matsodoum Nguemté et al., 2020 ). Model and experimental results showed that PAH concentrations can vary significantly between different compartments of plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting to note that numerous factors can dramatically alter the percentage contributions of ΣPAHs(3,4) and ΣPAHs(5,6). The influence of PAH molecular weights on the soil-plant transfer of PAHs was investigated using three short-life herbaceous species, namely Eleusine indica , Cynodon dactylon , and Alternanthera sessilis ( Matsodoum Nguemté et al., 2020 ). Model and experimental results showed that PAH concentrations can vary significantly between different compartments of plants.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Fluo and Pyr (i.e. LMW PAHs) tend to bioaccumulate in stem and leave compartments while HMW PAHs tend to occur in plant lipids and comparatively higher organic matter areas ( Balasubramaniyam, 2015 ; Matsodoum Nguemté et al., 2020 ). Because both lakes are surrounded by highly biodiverse herbaceous tropical plants, the impact of plant ab sorption on the alteration of percentage contributions of PAHs is undeniable.…”
Section: Resultsmentioning
confidence: 99%